2018
DOI: 10.1080/1461670x.2018.1423633
|View full text |Cite
|
Sign up to set email alerts
|

Reason Over Politics

Abstract: Adopting a critical perspective, this article examines how journalism has historically addressed austerity by analysing the austerity debates of the influential business magazine The Economist from 1947 to 2012. By analysing 131 articles with a qualitative frame analysis approach, I show how The Economist has used an enduring frame by which to position itself as the voice of reason against the irrationality of politics. It has typically framed austerity as necessary in times of economic distress, and political… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…The results of this article bear similarities with other studies on austerity, neoliberalism and the media. The article supports research findings emphasising that journalism has been incapable of challenging the dominant neoliberal discourses, which prioritise economic imperatives over democratic and political claims and render anti-austerity claims irrational or unreasonable (Harjuniemi, 2018;Kantola, 2007;Kelsey, Mueller, Whittle & KhosraviNik, 2016;Power et al, 2016). However, the article also found that The Economist evoked a nuanced debate on the effects of austerity in Europe; it was highly critical of European political elites, blaming them for being fixated on deepening the economic plight of Europe with ever-harsher austerity measures.…”
Section: Conclusion and Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…The results of this article bear similarities with other studies on austerity, neoliberalism and the media. The article supports research findings emphasising that journalism has been incapable of challenging the dominant neoliberal discourses, which prioritise economic imperatives over democratic and political claims and render anti-austerity claims irrational or unreasonable (Harjuniemi, 2018;Kantola, 2007;Kelsey, Mueller, Whittle & KhosraviNik, 2016;Power et al, 2016). However, the article also found that The Economist evoked a nuanced debate on the effects of austerity in Europe; it was highly critical of European political elites, blaming them for being fixated on deepening the economic plight of Europe with ever-harsher austerity measures.…”
Section: Conclusion and Discussionsupporting
confidence: 65%
“…Indeed, The Economist has traits that connect it with the more mainstream Western journalistic identity (Harjuniemi, 2018). Journalists have traditionally seen themselves as serving the people as the objective 'watchdog' (Deuze, 2005;Hanitzsch, 2011) of democracy, a professional identity comprised of such elements as truthfulness, independence, fairness and balance (Nerone, 2013;Tuchman, 1972).…”
Section: The Economist and The Austerity Casementioning
confidence: 99%
See 3 more Smart Citations